Mineral chemistry of apatite, amphibole, biotite, and magnetite from the Masjeddaghi porphyry Cu-Au deposit, NW Iran: petrogenetic and metallogenic implications - Rahnama, Zohreh; Hassanpour, Shohreh; Savard, Dany; Shah, Zahid (Frontiers in Earth Science, 2025)
The Masjeddaghi porphyry Cu-Au deposit is situated in the Alborz-Azarbaijan structural zone of northwest Iran. Chemical compositions of rock-forming (biotite, amphibole) and accessory minerals (magnetite, apatite) in the potassic to propylitic altered diorite porphyry of Masjeddaghi serve as key indicators of magmatic-hydrothermal mineralization. In situ LA-ICP-MS was conducted to analyze trace element contents of selected magnetite-bearing samples, while EMPA analyzed biotite, amphibole, and apatite compositions. The mineral compositions show a parental magma with calc-alkaline features, suggesting a source comprised of both subduction mantle-derived and crust-derived materials, and the Masjeddaghi mineralizing magmas have a relatively elevated ƒO2 and are classified as oxidized I-type magmas. The calculated temperature ranges are constrained by Al-in-amphibole geothermometry, saturation temperature of apatite, and the Ti-in-biotite geothermometer (830°C–877°C) (845°C-918°C) and (723°C–782°C), respectively, whereas the Al-in-amphibole geobarometry exhibits formation pressure (120–186 MPa; relating to depths ranging from 4 to 10 km) and H2Omelt content at time of crystallization (4.10–4.46 wt%), indicating formation of a hydrous calc-alkaline magma from a deep magmatic reservoir. The intrusion of oxidized hydrous mafic magma from a deeper magma source likely promoted wide magma mixing and prolonged fractional crystallization within the evolved dioritic magma chamber, resulting in exsolution of the ore-forming fluids and the formation of the Masjeddaghi deposit.